Jam’al-Qur’an Pada Masa Nabi, Khulafa’ Al-Rasyidin, Dan Sesudahnya - Hakmi Hidayat; Sinta Dilla Azizatul Wahidah; Amelia Dea Divanda; Aulia Ghani (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Hadith recording is not always a complex recording of the Qur'an. The Qur'an is the revelation of Allah because it is a book or a sheet of paper that is drawn and written.In order to prevent the Qur'an from drowning into the era, information about the collection of Qur'ân at the time of Khulafaurrasyidin should be disseminated frequently. This is especially true in the digital age, where interpretation is becoming important. Data is collected, read, recorded, and processed. Library data used in this research. This research is descriptive and analytical by analyzing the books of history and the interpretation of the Qur'an. Jam'ul Qur'an comes from the word "Jama'a yajma'u", which means gathering the opinions of scholars. The Qur'an is written letter by letter, as Allah has revealed to the Prophet (salla Allahu alihi wa sallam) and has spoken it in his heart. The attempts to improve the Utsmany mushaf, such as giving reading marks for points and syakls, forcing the Muslims to write the mushaf with writing (khat) as beautifully as possible, making signs to distinguish verses from one another, and more boldly listing surah names, number of verses, indication that the surah is Makkiyah or Madaniyah, and code that indicates the beginning of the verses.The process of printing the Qur'an continued to grow to a joyful event, besides the great meaning, that is, when a small, beautiful, fine version of the Quran appeared in Cairo.